Dysthymic disorder in the elderly population. (January 2014) - Devanand, D. P.
ABSTRACT The diagnosis of dysthymic disorder was created in DSM-III and maintained in DSM-IV to describe a depressive syndrome of mild to moderate severity of at least two years' duration that did not meet criteria for major depressive disorder. The prevalence of dysthymic disorder is approximately 2% in the elderly population where subsyndromal depressions of lesser severity are more common. Dysthymic disorder was replaced in DSM-V by the diagnosis of "persistent depressive disorder" that includes chronic major depression and dysthymic disorder. In older adults, epidemiological and clinical evidence supports the use of the term "dysthymic disorder." In contrast to young adults with dysthymic disorder, older adults with dysthymic disorder commonly present with late age of onset, without major depression and other psychiatric disorders, and with a low rate of family history of mood disorders. They often have stressors such as loss of social support and bereavement, and some have cerebrovascular or neurodegenerative pathology. A minority has chronic depression dating from youth with psychiatric comorbidity similar to young adults with dysthymic disorder. In older adults, both dysthymic disorder and subsyndromal depression increase disability and lead to poor medical outcomes. Elderly patients with dysthymic disorder are seen mainly in primary care where identification and treatment are often inadequate. Treatment with antidepressant medication shows marginal superiority over placebo in controlled trials, and problem-solving therapy shows similar efficacy. Combined treatment and collaborative care models show slightly better results, but cost effectiveness is a concern. Further work is needed to clarify optimal approaches to the treatment of dysthymic disorder in elderly patients.